PERAN BIDAN DALAM PELAKSANAAN PROGRAM PERENCANAAN PERSALINAN DAN PENCEGAHAN KOMPLIKASI (P4K) PADA MASA KEHAMILAN DI KOTA PEKALONGAN - Rosmiati Rosmiati; Tri Anonim; Supriyo Supriyo (JURNAL LITBANG KOTA PEKALONGAN, 2016)
THIS STUDY AIMS TO DESCRIBE THE ROLE OF A MIDWIFE AS A FASILITATOR, EDUCATOR, AND EXECUTING THE IMPLEMENTATION DURING THE PERIOD OF PREGNANCY IN P4K PEKALONGAN. EXPECTED RESULT CAN BE USEFUL TO RESEARCHERS, EDUCATIONAL INSTITUTATIONS AND THE MIDWIFE. THE DESIGN USED IN THIS STUDY IS A DESCRIPTIVE CROSS SECTIONAL APPROACH CORRELATIVE. SAMPLING BY MEANS OF NONPROBABILITY SAMPLING WHICH IS TOTALED 60 MIDWIFE. DATA COLLECTION IS DONE BY USING A CHECKLIST WHICH IS COMPLETED BY THE RESERCHERS AND THE ENUMERATOR IS. ANALYSIS OF THE DATA USED IS UNIVARIATE. RESULT OF THE ANALYSIS OF THE MAJORITY OF THE RESPONDENT’S CONDUCT: THE ROLE OF A MIDWIFE AS A FACILITATOR WITH THE HIGHEST SKORE (90%) AND THE LOWEST (15%), THE ROLE OF A MIDWIFE AS A EDUCATOR WITH HIGHEST SKORE (100%) AND THE LOWEST (15%), THE ROLE OF MIDWIFE AS A PERFORMER WITH THE HIGHEST SKORE (95%) AND THE LOWEST (15%). IT CANT BE CONCLUDED THAT THERE IS SOME MIDWIVES WHO HAVE NOT CARRIED OUT THE ROLE OF A MIDWIFE AS A FACILITATOR (26%), EDUCATOR (18%), AND THE EXECUTOR (24%) INTHE IMPLEMENTATION OF P4K DURING PREGNANCY, SO THE MIDWIFE NEEDS TO IMPROVE IMPLEMENTATION OF THE ROLE OF A MIDWIFE AS A FASILITATOR, EDUCATOR, AND IMPLEMENTING THROUGH KNOWLEDGE, AWARENESS IN UTILISING THE TIME IN SERVICE HOURS, AND FULL DEDICATION AS A PUBLIC HEALT OFFICER.